Panoramic view of Dawson, Yukon Territory, Nov. 21, 1899. - Goetzman, H. J.
Caption on image: "Dawson, Y.T. Nov. 21 - 99" PH Coll 246.46 [Meed journal: "Dawson, Y.T. Nov. 21st 1899. Looking up-stream. The snowfall is not heavy, and the particles are fine, dry and powdery. Temperature usually 40 to 50 degrees and has reached 68 degrees below zero. Steamers seen are frozen in."] To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number